Leveraging real‐time data to drive quality improvement in a pediatric health system - Bhattarai, Sopnil (Pediatr Investig, 2018)
We are inundated by data; healthcare is no different. The electronic medical record, the numerous patient care monitors, and the thousands of medications to be reconciled with specific dosing parameters are a few examples of the omnipresent and intimidating nature of data in healthcare. Across the world, healthcare without data does not exist. The data represent many forms but are quickly moving towards electronic formats. As ubiquitous as data are the near universal finding that such data are lagging. There is an urgent need for real‐time data in improving processes and ultimately outcomes in healthcare. If data lag by four to eight weeks, if not longer, then true change cannot occur and harm continues in that interval. This review article discusses the urgent need for real‐time data and demonstrates examples of how Children's National Medical Center in Washington, DC uses real‐time data to drive outcomes.